Age Related Changes of Submandibular Salivary Glands (Ultrasonographic and Structural Study) - Ghanim Abdulla , Ali; .J.Kazim , Talib; salem , Abdulkareem (Diyala Journal of Medicine, 2019)
Back ground :- The present study introduced the age changes in the parameters of the submandibular salivary glands (SMSGs) of twenty-four volunteers subjects. Aims: ultrasonographical and structural age changes study of sub mandibular salivary glands in living human and cadavers. Materials and methods: the study considered ; twenty four volunteers and sixteen male cadavers. The cadaver's weighed and grouped according to ages; G (A) 20-25 years, (B) 30-35 years, (C); 45-50 years, and group (D) 60-70 years. The same grouping manner applied to the ultrasonographic study. Cadavers with diseased history of the (SMSGs), or maxillofacial trauma were excluded. Results; The histological findings revealed that there was; a decrease in the number of serous demilunes, but an increase in the diameter of both serous and mucous acini with, proportional increases of the serous acini, and an increase in the diameter of striated ducts during the increase of age. The thickness of the interlobular connective tissue were increased with advancing age, as well as the number of adipose cells. Conclusion; The sonographic, and gross anatomical parameters showed little but no significant changes during the ages considered in this experimentation, so for the weight and dimensions of the glands.